Neurophysiological Differences Between Women With Fibromyalgia and Healthy Controls During Dual Task: A Pilot Study - Villafaina, Santos; Fuentes-García, Juan Pedro; Cano-Plasencia, Ricardo; Gusi, Narcis (Frontiers in Psychology, 2020)
Background: Women with FM have a reduced ability to perform two simultaneous tasks. However, the impact of dual-task (DT) on the neurophysiological response of women with FM has not been studied. Objective: To explore both the neurophysiological response and physical performance of women with FM and healthy controls while performing a DT (motor-cognitive). Design: Cross-sectional study. Methods: A total of 17 women with FM and 19 age- and sex-matched healthy controls (1:1 ratio) were recruited. The electroencephalographic (EEG) activity was recorded while participants performed two simultaneous tasks: a motor (30 seconds arm-curl test) and a cognitive (remembering three unrelated words). Theta (4-7 Hz), alpha (8-12 Hz) and beta (13-30) frequency bands were analyzed by using EEGLAB. Results: Significant differences were obtained in the healthy control group between single-task (ST) and DT in the theta, alpha, and beta frequency bands (p-value < 0.05). Neurophysiological differences between ST and DT were not found in women with FM. In addition, between-groups differences were found in the alpha and beta frequency bands between healthy and FM groups, with lower values of beta and alpha in the FM group. Therefore, significant group*condition interactions were detected in the alpha and beta frequency bands. Regarding physical condition performance, between groups, analyses showed that women with FM obtained significantly worse results in the arm curl test than healthy controls, in both ST and DT. Conclusions: Women with FM showed the same electrical brain activity pattern during ST and DT conditions, whereas healthy controls seem to adapt their brain activity to task commitment. This is the first study that investigates the neurophysiological response of women with FM while simultaneously performing a motor and a cognitive task.